Citrus Nursery Production Guide, Chapter 8: Stock Plant and Tree Production: c) Weed Management in Citrus Nurseries - Biwek Gairhe; Ramdas Kanissery; Brent Sellers (EDIS)
All citrus nursery stock in Florida is raised in enclosed greenhouses. It is not uncommon for weeds to grow in containers, where they compete with citrus seedlings, and on greenhouse floors, where they can harbor pests and diseases. This new 7-page publication of the UF/IFAS Horticultural Sciences Department provides descriptions of a few commonly found weeds in citrus nurseries and good weed management practices. Written by Biwek Gairhe, Ramdas Kanissery, and Brent Sellers, this article is chapter 8c of the forthcoming Citrus Nursery Production Guide. https://edis.ifas.ufl.edu/hs1344